2004
DOI: 10.1523/jneurosci.0963-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Y99C Mutation in Guanylyl Cyclase-Activating Protein 1 Increases Intracellular Ca2+and Causes Photoreceptor Degeneration in Transgenic Mice

Abstract: Guanylyl cyclase-activating proteins (GCAPs) are Ca 2ϩ -binding proteins that activate guanylyl cyclase when free Ca 2ϩ concentrations in retinal rods and cones fall after illumination and inhibit the cyclase when free Ca 2ϩ reaches its resting level in the dark. Several forms of retinal dystrophy are caused by mutations in GUCA1A, the gene coding for GCAP1. To investigate the cellular mechanisms affected by the diseased state, we created transgenic mice that express GCAP1 with a Tyr99Cys substitution (Y99C GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
127
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(135 citation statements)
references
References 52 publications
(70 reference statements)
7
127
1
Order By: Relevance
“…Triple RetGC2 Ϫ/Ϫ GCAPs1,2 Ϫ/Ϫ (11) gene knock-out mice lack RetGC2 isozyme and both GCAPs altogether, but RetGC1 in these retinas is expressed at a normal ratio to rhodopsin and preserves its activation and normal Ca 2ϩ -sensitive regulation in the presence of exogenously added GCAP1 and GCAP2 (11). Note that this cyclase assay in whole retina specifically measures activity of RetGC from photoreceptors (11,33,34). We found that the native RetGC1 in the triple knock-out retinas saturated by GCAP1 did not increase its activity when GCAP2 was also added in the same assay.…”
Section: Resultsmentioning
confidence: 99%
“…Triple RetGC2 Ϫ/Ϫ GCAPs1,2 Ϫ/Ϫ (11) gene knock-out mice lack RetGC2 isozyme and both GCAPs altogether, but RetGC1 in these retinas is expressed at a normal ratio to rhodopsin and preserves its activation and normal Ca 2ϩ -sensitive regulation in the presence of exogenously added GCAP1 and GCAP2 (11). Note that this cyclase assay in whole retina specifically measures activity of RetGC from photoreceptors (11,33,34). We found that the native RetGC1 in the triple knock-out retinas saturated by GCAP1 did not increase its activity when GCAP2 was also added in the same assay.…”
Section: Resultsmentioning
confidence: 99%
“…Although it remains unclear why excess stimulation would do this, our best guess at present is that continuous activation triggers apoptosis by producing a prolonged lowering of the Ca 2þ concentration. Since high Ca 2þ can also kill photoreceptors, (49) these cells appear to tolerate a Ca 2þ concentration only within a restricted range, much as has been proposed for neurons. (91) Future experiments with animal models having altered cyclic nucleotidegated channels and transporters may help define this range with more precision.…”
Section: Resultsmentioning
confidence: 99%
“…48), and high outer segment Ca 2þ has recently been indicated as a probable precipitator of apoptosis in some kinds of retinal degenerations. (49) For Ca 2þ to be the agent of death during continuous light and vitamin A deprivation, however, apoptosis would have to be triggered not by an increase in Ca 2þ but rather by a maintained decrease. In real or equivalent background light, the probability of opening of a cGMP-gated channel decreases (Fig.…”
Section: Why Does Continuous Activation Kill?mentioning
confidence: 99%
“…Because the mutant cyclase binds the activator form of GCAP1 with higher affinity (44 -46), it now takes higher Ca 2ϩ concentrations, converting a larger fraction of GCAP1 into the inhibitor state, to outcompete the activator form of GCAP1 and decelerate the cyclase (46). Deregulation of RetGC1 is the main reason for photoreceptor death in mouse models expressing Y99C or E155G GCAP1 mutants (58,62,63). When RetGC1 deceleration by Ca 2ϩ in the dark becomes less sensitive, a larger fraction of cGMP-gated channels in the plasma membrane maintains Ca 2ϩ influx in the dark, eventually provoking the onset of apoptosis (62,63).…”
Section: What Processes Downstream Of the Mutated Cord6 Retgc1 Causementioning
confidence: 99%
“…Deregulation of RetGC1 is the main reason for photoreceptor death in mouse models expressing Y99C or E155G GCAP1 mutants (58,62,63). When RetGC1 deceleration by Ca 2ϩ in the dark becomes less sensitive, a larger fraction of cGMP-gated channels in the plasma membrane maintains Ca 2ϩ influx in the dark, eventually provoking the onset of apoptosis (62,63). Stimulation of cGMP-dependent protein kinase activity can also lead to mouse photoreceptor death independently of the Ca 2ϩ pathway (64,65).…”
Section: What Processes Downstream Of the Mutated Cord6 Retgc1 Causementioning
confidence: 99%